Effects of Supply Chain Flexibility towards Supply Chain Collaboration and Supply Chain Agility - Noriza Mohd Jamal; Wee Sin Yi; Thoo Ai Chin; Norhalimah Idris (International Journal of Supply Chain Management, 2019)
Facing uncertain environment, the cultivation of agility is approached as a strategic ability that assists organizations rapidly to sense and respond internal and external uncertainties via effective collaboration of supply chain relationships. The objective of the study is to uncover how organizational antecedent, supply chain collaboration (SCC) and organizational competency, supply chain flexibility (SCF), aimed at augmenting the supply chain agility (SCA) of firms. To take advantage of available market opportunities, firms would see the supply chain that are flexible will outperform those are less agile. Thus, SCF has emerged as a vital management strategy to strengthen the relationship between SCC and SCA as firms will be more flexible and responsive to an unpredictable environment and cope with ever changing customers requirements. In this paper, an attempt is made to present a conceptual model of the organizational antecedents that affect the agility of supply chain in the context of small and medium manufacturing firms.